A study on the effects of uniaxial cyclic tensile loading on human bone marrow derived-mesenchymal stromal cells In Vitro / Nam Hui Yin - Nam, Hui Yin (2017)
Mesenchymal stromal cells (MSCs), being multipotent cells, have the ability to undergo both self-renewal and multi-lineage differentiation. Although many techniques to drive cellular response using chemical or hormonal cues have been described, the use of mechanical loading as a method to harness the potential of MSCs has not been fully realized. In tendons especially, mechanical stimulation modulates cellular proliferation and tenogenic expression/differentiation thereby regulating tissue homeostasis. Similar to MSCs, the exact mechanisms involved in the process of converting mechanical signals into cellular differentiation have yet to be elucidated. For this reason, the present thesis comprising of several key studies was conducted to assist us in getting us closer to better understand the possible mechanisms underpinning these aforementioned laboratory and clinical observations. In the present study we hypothesized that uniaxial cyclic loading is expected to improve cellular and direct tenogenesis differentiation through the activation of ion channels. The studies were conducted with the following aims: 1) to demonstrate that cells proliferation can be regulated through mechanical loading, 2) to determine the parameters that will lead to superior tenogenic differentiation of human MSCs (hMSCs), 3) to determine the role of ion channels, specifically epithelium sodium channel (ENaC) and stretch-activated calcium channel (SACC), in regulating the observations made in aims 1 and 2. To achieve the first aim of this study, hMSCs were isolated, expanded, and subjected to cyclical uniaxial stretching of 4%, 8% or 12% strain at 0.5 Hz or 1 Hz for 6, 24, 48 or 72 hours. This was compared to unstrained hMSC cultures. Morphology and alignment of the cells was documented, whilst cell viability and proliferation were assessed using live/dead cell staining and alamarBlue assay. The result demonstrates that strained cells appear to be realigned perpendicular to the direction of tensile loading in contrast to unstrained cells, which were arranged randomly. The highest cell proliferation was observed when 4% iv strain+1 Hz was applied (p < 0.05). To obtain aim 2, hMSCs differentiation was analysed using cells topography, immunostaining, immunofluorescent staining, biochemical assays and mesenchymal cell gene expression markers. At 8% and 12% strain (1 Hz), an increase in collagen I, collagen III, elastin, fibronectin, and N-cadherin production were observed; but not for collagen II and glycosaminoglycans. Tenogenic genes expression were only highly expressed when subjected to 8% and 12% (p < 0.05), although in the former it was higher. The osteoblastic, chondrogenic and adipogenic marker genes appeared to be down-regulated. Lastly, the tenogenic differentiation of hMSCs was examined in the presence and absence of ENaC and SACC by adding benzamil and gadolinium, respectively. The results show that by inhibiting these two mechanosensitive channels, mechanical stretching retards biochemical signalling queues and that stretch-induced tenogenic differentiation process is aborted. In conclusion, the observations of our studies suggests that MSCs are sensitive to mechanical stimulation specifically to tenogenesis response, and can be regulated by altering certain parameters such as ion channel sensitivity, duration of stretching and, rate and amounts of strains.